Paisaje lingüístico en Benín: un recurso didáctico y motivador para el aula de lenguas extranjeras - Sossouvi, Laurent-Fidèle; Lin, Mei-Chih (Linguistik Online, 2020)
Multilingualism and multiculturalism have been and are constitutive aspects of African soci-eties. This pioneer study analyzes the linguistic landscapes of Cotonou and Abomey-Calavi (Benin), two contiguous cities; in order to verify the status and the vitality of the languages used and spoken in the country as well as seeing if it is possible to exploit didactically this written modality. For this purpose, a quantitative analysis of written language productions in public space was carried out. The results reveal the languages used in the urban scene of both cities as well as the linguistic contact in their diverse aspects. They also indicate that the linguistic landscape doesn’t take into account the local multilingual practices in all their complexity. It appears as a context of learning which can be used as a didactic resource in the teaching of foreign languages.